(untitled) (Agriculture, Food, and Natural Resources Journal, 2024)
This study examined selected wood qualities of Tectona grandis Linn. F. plantation in the University of Ibadan, Nigeria for sustainable Management. Five even-aged merchantable teak stands with diameter at breast height (DBH) ≥ 50 cm were randomly felled. Wood samples from DBH, base (10%), middle (50%), and top (90%) axial positions and partitioned into radial zones (core, middle, and outer growth rings). The physical properties: Moisture Content (MC), Density(D), Longitudinal Shrinkage (LS), Radial Shrinkage (RS), Tangential Shrinkage (TS), and Volumetric Shrinkage (VS), and mechanical properties: Dimensional Stability (DS), Modulus of Elasticity (MOE), Modulus of Rupture (MOR), and Maximum Compressive Strength (MCS) were determined using standard procedures. Data collected were subjected to descriptive, analysis of variance and correlation analyses. Significant means were separated using Least significant difference. The results revealed that MC, D, LS, RS, TS and VS had pooled means (axial and radial variations) of 12.18%, 636.08kg/m3, 2.22%, 3.98%, 3.84%, and 7.81% respectively. Wood density and shrinkage coefficients varied slightly across the axial and radial positions of the stands. The DS, MOE, MOR and MCS (parallel to the grain) had pooled means of 1.85, 985.46N/mm2, 43.30N/mm2, and 49.20 N/mm2, respectively. Significance (p<0.05) were recorded across all the radial axis. A positive and significant correlation was observed between MOE and MOR. The study concludes that the plantation had more dense wood which contributes to stronger and more durable wood, making it suitable for various structural applications. Hence, regular silvicultural management practices are recommended to maintain the wood stiffness, strength and dimensional stability.